Community Supervision in the Development of the North Bandung Region - Asep Sumaryana (Khazanah Sosial, 2023)
The North Bandung Area (KBU) is experiencing rapid development, despite its designation as a water conservation area. This designation holds potential for reforestation and benefits the ecological interests of the local community and downstream areas. However, despite the implementation of binding policies aimed at preserving the area, it is evident that damage has occurred. This research adopts a qualitative approach with descriptive methods to investigate the reasons behind this phenomenon. The research findings indicate a continuous weakening of social supervision, attributed to changes in community orientation and a lack of courage to protect the environment. The community's involvement in social supervision could be improved, but the weakening government protection exacerbates the situation. Consequently, the neglect persists, and some individuals exploit the situation for their own interests.